Digital Audio Technologies, Audio Mixing and Sound Effects - Neal, Titus, author 641437; Nigel, Mccarthy, author 647995 (Delhi, India : College Publishing House, 2012)
This is a well written thorough Handbook of Digital Audio Technologies, Audio Mixing and Sound Effects.